CCAFS 4 dimensions gender inequality - Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
A recent review of literature and regional case studies with researchers from four regions identified the critical dimensions of gender in/ equality in climate-resilient agriculture. They are: (1) participation in decision-making at different levels, (2) work burden, (3) access to and use of productive resources such as agroclimatic information, technology, livelihood incomes, and credit, and (4) collective action. Models for action are presented that show how gender-responsive approaches can promote equality while increasing resilience for all.